Disproportionate Mitral Regurgitation Determines Survival in Acute Heart Failure - Berrill, Max; Beeton, Ian; Fluck, David; John, Isaac; Lazariashvili, Otar; Stewart, Jack; Ashcroft, Eshan; Belsey, Jonathan; Sharma, Pankaj; Baltabaeva, Aigul (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To assess the prevalence and impact of mitral regurgitation (MR) on survival in patients presenting to hospital in acute heart failure (AHF) using traditional echocardiographic assessment alongside more novel indices of proportionality. Background: It remains unclear if the severity of MR plays a significant role in determining outcomes in AHF. There is also uncertainty as to the clinical relevance of indexing MR to left ventricular volumes. This concept of disproportionality has not been assessed in AHF. Methods: A total of 418 consecutive patients presenting in AHF over 12 months were recruited and followed up for 2 years. MR was quantitatively assessed within 24 h of recruitment. Standard proximal isovelocity surface area (PISA) and a novel proportionality index of effective regurgitant orifice/left ventricular end-diastolic volume (ERO/LVEDV) >0.14 mm2/ml were used to identify severe and disproportionate MR. Results: Every patient had MR. About 331/418 (78.9%) patients were quantifiable by PISA. About 165/418 (39.5%) patients displayed significant MR. A larger cohort displayed disproportionate MR defined by either a proportionality index using ERO/LVEDV > 0.14 mm2/ml or regurgitant volumes/LVEDV > 0.2 [217/331 (65.6%) and 222/345 (64.3%), respectively]. The LVEDV was enlarged in significant MR−129.5 ± 58.95 vs. 100.0 ± 49.91 ml in mild, [p < 0.0001], but remained within the normal range. Significant MR was associated with a greater mortality at 2 years 44.2 vs. 34.8% in mild MR [hazard ratio (HR) 1.39; 95% CI: 1.01–1.92, p = 0.04], which persisted with adjustment for comorbid conditions (HR; 1.43; 95% CI: 1.04–1.97, p = 0.03). Disproportionate MR defined by ERO/LVEDV >0.14 mm2/ml was also associated with worse outcome [42.4 vs. 28.3% (HR 1.62; 95% CI 1.12–2.34, p = 0.01)]. Conclusions: MR was a universal feature in AHF and determines outcome in significant cases. Furthermore, disproportionate MR, defined either by effective regurgitant orifice (ERO) or volumetrically, is associated with a worse prognosis despite the absence of adverse left ventricular (LV) remodeling. These findings outline the importance of adjusting acute volume overload to LV volumes and call for a review of the current standards of MR assessment. Clinical Trial Registration:https://clinicaltrials.gov/ct2/show/NCT02728739, identifier NCT02728739.